Comparing the Effect of oral Clonidine and Tranexamic Acid on Bleeding During Rhinoplasty Under General Anesthesia: A Clinical Trial - Akram Hemmatipour; Amin Ali Konari; Hamid Reza Samii; Azam Jahangiri Mehr; Fateme Moshtaghi (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Bleeding during rhinoplasty is a complication that causes the surgeon to lose vision and will cause other complications. So far, various methods have been proposed to reduce bleeding during nose surgery. The present study aims to compare the effect of oral clonidine and tranexamic acid on intraoperative bleeding in patients undergoing rhinoplasty. Materials and methods: In this randomized, double-blind clinical trial, 120 patients who were candidates for elective rhinoplasty surgery were included. In the first group, three µg/kg of clonidine was administered orally 90 minutes before surgery. In the second group, 250 µg/kg bw tranexamic acid capsules were administered orally two hours before surgery. There was no intervention in the control group. Bleeding levels, hemodynamic parameters, and surgeons' visual satisfaction were evaluated. Results: The mean age of patients (28.67±5.35) years and 96 (80.0%) were women. Regarding the effect of drug and surgeon’s visual satisfaction, there is a significant difference between the clonidine and tranexamic acid groups (P=0.055); the mean bleeding volume in the clonidine group was 112.0±0.47 and in the tranexamic acid group was 132.0±0.36. In addition, the clonidine group (P=0.008) and tranexamic acid (P<0.001) showed a significant difference in terms of bleeding volume compared with the control group (195.0±28.1). The three variables of drug type, weight, and duration of anesthesia can explain and predict 51% of the changes (blood volume). Conclusion: The results of the present study showed that clonidine can be more effective in reducing bleeding than tranexamic acid, and by creating a relatively dry and bleeding-free environment, it can improve the quality of the surgeon’s vision and reduce the duration of rhinoplasty surgery.